Effects of embedded multimedia in directed reading lessons on student engagement and media analysis - Verzo, Emmanuel B. Jr (Alipato : a Journal of Basic Education, 2017)
Access online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/5783